Closing productivity gaps among Dutch dairy farms can boost profit and reduce nitrogen pollution. (15th November 2021) - Lamkowsky, Melina; Oenema, Oene; Meuwissen, Miranda P M; Ang, Frederic
Abstract: Agricultural productivity growth can simultaneously increase profit and reduce pollution. Yet, the impact of productivity growth on both has not been quantified. The objective of our study was to develop an approach to quantify the extent to which agricultural productivity growth can increase profit and reduce pollution. Focusing on nitrogen pollution, we applied the approach to a sample of 341 intensive Dutch dairy farms for the years 2006–2017. Using a Bennet–Lowe formulation, we measured economic and nitrogen productivities over time and across farms. We applied Data Envelopment Analysis to determine the potential for productivity growth from reducing economic and nitrogen inefficiencies and assessed the impact on profit and nitrogen pollution levels. Using a two-stage by-production model, we set profit maximisation as the overarching objective to account for the economic production behaviour of farmers. We found that if laggard farmers adopted the best practices of their best peers, they could on average increase annual gross profit by 34% and simultaneously reduce the N surplus by 50% during the time period, which is a win–win situation for farmers and the environment. The magnitude of these gains corroborates the suggestion that productivity growth could be a game-changer for agricultural sustainability.